Synthesis of coil‐comb block copolymers containing polystyrene coil and poly(methyl methacrylate) side chains via atom transfer radical polymerization. Issue 18 (10th June 2016) - Shin, Seonhee; Moon, Seohyun; Seo, Myungeun; Kim, Sang Youl
ABSTRACT: A series of polystyrene‐ b ‐(poly(2‐(2‐bromopropionyloxy) styrene)‐ g ‐poly(methyl methacrylate)) (PS‐b‐(PBPS‐g‐PMMA)) and polystyrene‐ b ‐(poly(2‐(2‐bromopropionyloxy)ethyl acrylate)‐ g ‐poly(methyl methacrylate)) (PS‐ b ‐(PBPEA‐ g ‐PMMA)) as new coil‐comb block copolymers (CCBCPs) were synthesized by atom transfer radical polymerization (ATRP). The linear diblock copolymer polystyrene‐ b ‐poly(4‐acetoxystyrene) and polystyrene‐ b ‐poly(2‐(trimethylsilyloxy)ethyl acrylate) PS‐ b ‐P(HEA‐TMS) were obtained by combining ATRP and activators regenerated by electron transfer (ARGET) ATRP. Secondary bromide‐initiating sites for ATRP were introduced by liberation of hydroxyl groups via deprotection and subsequent esterification reaction with 2‐bromopropionyl bromide. Grafting of PMMA onto either the PBPS block or the PBPEA block via ATRP yielded the desired PS‐ b ‐(PBPS‐ g ‐PMMA) or PS‐ b ‐(PBPEA‐ g ‐PMMA). 1 H nuclear magnetic resonance spectroscopy and gel permeation chromatography data indicated the target CCBCPs were successfully synthesized. Preliminary investigation on selected CCBCPs suggests that they can form ordered nanostructures via microphase separation. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 2971–2983 Abstract : Coil‐comb block copolymers containing PS coils and PMMA side chains were synthesized by ATRP and their microphase separation behavior was studied.